ROLE OF TECHNOLOGICAL INNOVATIONS IN THE TRANSFORMATION OF THE US REHABILITATION SYSTEM IN THE 1990S–2020S - Fedinskyi, Oleksii (SWorld-Ger Conference proceedings, 2025)
The article examines the main stages of technological modernization of the US rehabilitation system in the 1990s–2020s. It analyzes the impact of legal reforms (Americans with Disabilities Act, Section 508 Amendment) on the formation of digital accessibil